Initiation of walking in submerged and non-submerged conditions: An electromyographic study - Kaneda, K. (XIII th International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2018)
The initiation of walking is an important task for the transition from standing to cyclic walking in daily life. Currently, there are no reports on muscle activity during the initiation of walking in a submerged condition. This study recruited eight participants. They performed three experimental trials of walking a few steps in submerged and non-submerged conditions. During the trials, surface electrodes were attached to the participant`s right side lower extremity and trunk muscles. The mean muscle activity of the tibialis anterior (TA) and erector spinae (ES) muscles was significantly higher in the submerged condition than in the non-submerged condition. In contrast, the mean muscle activity of the gastrocnemius (GAS) and rectus abdominis (RA) muscles was significantly lower in the submerged condition. The integrated muscle activity of the TA, RF, and ES muscles was significantly higher in the submerged condition. This suggests that a large muscle load was placed on the TA and ES muscles, and a low level of stimulation but long muscle load was placed on the GAS and RA muscles during the initiation of walking in the submerged condition. The longer muscle stimulation of the RF would promote a larger muscle load during the initiation of walking in a submerged condition. Our results suggest that walking in submerged conditions shows promise as a training and rehabilitation tool to help frail patients to maintain the ability to take the first step in walking.